TINGKAT KELAYAKAN TES UAS BAHASA ARAB PADA FAKULTAS ILMU TARBIYAH DAN KEGURUAN DI UIN SULTHAN THAHA SAIFUDDIN JAMBI TAHUN AJARAN 2016-2017 - Wahyudi, Wahyudi (Jurnal Al-Ashlah, 2017)
English :After conducting learning and teaching process, a lecturer is demanded to know the extent of the instructional objectives has been reached or to know studentsâ ability in mastering submitted object. One of the tools which is used to get information about instructional objectives reaching and studentsâ ability in mastering subject is test. To get accurate information above, a test must have criteria of good test, they are valid, reliable and also it has acceptable difficulty and discriminating power.Analysis item test of final test school of Arabic language subject of the student at FITK UIN STS Jambi is a research to the test of summative learning result that is made by the team of question arranging. This researcher is done to describe about: 1) Kind of test in last examination at first semester, 2) Quality of the test that is seen discriminating view, 3) The causes of the teacher not to do this analysis this test.This research is used descriptive method that use qualitative approach with the quantitative and qualitative data. The population of this research is all of students Arabic Language at the first semester that follow the examination in academic year 2016-2017 in FITK UIN STS Jambi spcially in Arabic Language subject, and the sample was taken in this research is students follow the examination at first semester for Arabic language subjet in Arabic Language Department with Purposive Sampling.Technique of data collecting is technique of documentation, interview and questioner. To analyze datum,the researcher uses percentage formula for validity,Cronbach Alpha for reliability,difficulty formula and discriminating formula.The data are collected using two instruments :(1) direct observation on test items sheet and its answer key sheet of final test of Arabic and,(2) through the result of the answer sheet of students taken as samples.The results of this research are : (1) the test forms are achievement test (instructional objectiveâs point of view), teacher-made test (the writerâs point of view), summative test (on timing of test), written test (executionâs point of view),and subjective test (the way of giving scoreâs point of view.(2) The qualities of Arabic language subject of the student At FITK UIN Sulthan Thaha Saifuddin Jambi are : (a) Validity of the test is good because it fulfills of the contents validity (b) Reliability test is higher at 0, 74,(c). Dificulty level test is very easy at 11,11%%. (d). Descrimination test is not good at 22,22%.(3)Causes of the teacher did not do the analysis test are:(a) There is lack of understanding of the analysis problem, (b) They have no experiment in doing the analysis test, (c) Less understand the ins and outs revalues,(d) Less understand problems analyze and,(e) There is teacher that has not gotten an exercise or seminar in the evaluation and analysis field.Â Indonesia :Penelitian ini mengunakan metode deskriptif dengan data kuantitatif dan data kualitatif. Adapun populasi dalam penelitian ini adalah mahasiswa jurusan Tadris pada Fakultas Ilmu Tarbiyah dan Keguruan yang mengikuti tes ujian akhir semester tahun ajaran 2016-2017 khususnya mata pelajaran bahasa arab. Maka sample yang diambil dalam penelitian ini adalah mahasiswa yang mengikuti ujian akhir semester pada mata kuliah bahasa arab pada jurusan Tadris (Pendidikan Matematika, Pendidikan Biologi, Pendidikan Fisika Dan Pendidikan Bahasa Inggris), dengan menggunakan teknik (Purposive Sampling).Teknik pengumpulan datanya adalah teknik dokumentasi, wawancara atau interview dan angket. Adapun rumusan yang digunakan untuk analisis data adalah rumus presentase untuk validitas isi, rumus Cronbach Alfha untuk reliabilitas, rumus tingkat kesulitan dan rumus daya pembeda. Data yang dikumpulkan ada dua cara yaitu observasi langsung terhadap lembar soal dan kunci jawaban tes ujian akhir tahun ajaran 2016-2017 mata pelajaran bahasa arab serta melalui hasil lembar jawaban terhadap beberapa mahasiswa yang menjadi sample dalam penelitian.Hasil penelitian ini adalah (1) jenis-jenis tes ini adalah tes hasil belajar/ achievement test dari segi tujuan pengajaran, tes buatan guru/ teacher-made test dari segi cara penyusunan, tes sumatif/ summative test dari segi waktu penyelenggaran, tes tertulis dari segi cara mengerjakannya dan tes subyektif dari segi menilai jawaban, (2) Kualitas tes Ujian Akhir Semester mata pelajaran bahasa Arab tahun ajaran 2016/2017: (a) Validitas tes baik, karena telah memenuhi validitas isi, (b) Reliabilitas tes tinggi yakni sebesar 0,74, (c) Tingkat kesulitan tes mudah sekali maka tes soal tersebut dikategorikan tidak baik yakni sebesar 45 butir soal atau 11,11%.(d) Tingkat daya pembeda tes kurang baik maka butir soal tes tersebut dikategorikan tidak baik yakni sebesar 45 butir soal atau 22,22%.(3) Sebab-sebab dosen atau team pembuat soal tidak melakukan analisis tes adalah sebagai berikut: (a) Sebagian besar dosen bahasa Arab pada Fakultas Ilmu Tarbiyah dan Keguruan di UIN Sulthan Thaha Saifuddin Jambi tidak berasal dari Sarjana Pendidikan Bahasa Arab atau tidak lenier dengan sarjana S-1 dengan S-2, (b) Tidak mempunyai pengalaman melakukan analisis tes, (c) Tidak adanya saran atau perintah dari atasan yang memotivasi dosen atau team pembuat soal melakukan analisis tes, (d) Kurang mengerti tentang permasalahan analisis, dan (e) Adanya pengajar/pendidik yang belum mendapatkan pelatihan atau seminar di bidang evaluasi dan analisis.